The impact of human resource management practices on service recovery performance - Khanfar, Fayiq (Opción, 2020)
Service failure and recovery remain important issues for both academicians and researchers in recent years. This study examines the direct empirical relationship between human resource management (HRM) practices on service recovery performance in United Arab Emirates – Abu Dhabi’s Healthcare Sectors. Results show that all the predictors have significant and insignificant effects on service recovery performance with service technology support. This study implies that HRM of healthcare in UAE should come forward and try their best to present a better work environment for employees to enhance service recovery performance to maintain customers’ satisfaction.